2017
DOI: 10.1039/c6sm02785g
|View full text |Cite
|
Sign up to set email alerts
|

Large strain viscoelastic dissipation during interfacial rupture in laminated glass

Abstract: In the dynamic rupture of laminated glass, it is essential to maximize energy dissipation. To investigate the mechanisms of energy dissipation, we have experimentally studied the delamination and stretching of a polymeric viscoelastic interlayer sandwiched between glass plates. We find that there is a velocity and temperature domain in which delamination fronts propagate in a steady state manner. At lower velocities, fronts are unstable, while at higher velocities, the polymer ruptures. Studying the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
1
28
1
Order By: Relevance
“…Currently, there is little doubt regarding the role of frictional energy dissipation during sliding of geckos [43,52] and other climbing animals [53]. The frictional sliding of elastomers pulled in shear is also supported by an increasing number of experimental studies [44,50,[53][54][55], and the phenomenon was recently observed in shearing of microstructured adhesives [38]. Frictional sliding is one consequence of the shear lag zone and refers to elastomer elongation while it is still in contact; this causes frictional energy dissipation.…”
Section: Frictional Slidingmentioning
confidence: 95%
See 1 more Smart Citation
“…Currently, there is little doubt regarding the role of frictional energy dissipation during sliding of geckos [43,52] and other climbing animals [53]. The frictional sliding of elastomers pulled in shear is also supported by an increasing number of experimental studies [44,50,[53][54][55], and the phenomenon was recently observed in shearing of microstructured adhesives [38]. Frictional sliding is one consequence of the shear lag zone and refers to elastomer elongation while it is still in contact; this causes frictional energy dissipation.…”
Section: Frictional Slidingmentioning
confidence: 95%
“…Once the maximum contact area is reached during wedge engagement, the contact front will be subjected to a force that will result in a decaying stress along the contact length (shear lag zone). Once a threshold tangential force is reached, the contact front will start sliding on the substrate without detaching forming a frictional sliding zone and its length will depend on the interfacial adhesion [44,50,[53][54][55]. If the frictional sliding zone does not extend to the end of the contact length, the front of the microwedge will slide without wedge relaxation.…”
Section: Friction Profile Typesmentioning
confidence: 99%
“…The TCTT was at the center of Paul Elzière's PhD thesis (Elzière 2016;Elzière et al 2017). In the TCTT, it is not straightforward to derive an elastic energy release rate, due to the highly dissipative nature of the polymer materials, which induces a coupling between debonding and large dissipative stretch.…”
Section: The Steady-state Regimementioning
confidence: 99%
“…This subject is related to the impact resistance of laminated glass, an industrial product made of a polymer foil-the interlayer-sandwiched between two glass plies. Previous work on impact resistance of laminated glass showed that for an impacting object of a few kilograms falling on a laminated glass at velocity typically between 1 and 10 m/s, the majority of the kinetic energy is converted into delamination and stretching of the interlayer (Nourry 2005;Elzière et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also for the SGP, they could not successfully implement the same methods proposed by Seshadri. Other authors such as Vam Dam [13] and Elzière et al [14] have also carried out work on this topic. Additionally, further researchers have conducted studies on the numerical response of laminated glass subject to impact loading [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%